Conscientiousness dan phubbing pada mahasiswa: Menguji peran kepuasan hidup sebagai moderator: Conscientiousness and phubbing in college students: Testing the role of life satisfaction as a moderator - Kiswantomo, Heliany; Rahmani, Kristin; Rakapurwa, Naufal (Persona:Jurnal Psikologi Indonesia, 2025)
Phubbing, or the phenomenon of cell phone use by college students when interacting with others, is a phenomenon that requires careful attention. This neglect of others and a greater focus on cell phone use makes phubbing a cause for concern, as it impacts students' academic and social relationships. Factors influencing phubbing are conscientiousness and life satisfaction. This study aimed to explore whether life satisfaction moderates the effect of conscientiousness on phubbing in college students. This study involved 306 college students recruited through convenience sampling. The measurement instruments used were the Satisfaction with Scale (α=0,868), the Phubbing Scale (α=0,990), and conscientiousness (α=0,614). Moderation analysis was used for data analysis. The results revealed that life satisfaction did not significantly moderate the effect of conscientiousness on phubbing in college students. Conscientiousness remained influential on phubbing, regardless of the students' level of life satisfaction. This condition is suspected to be related to cognitive flexibility and failure experiences, which could be confounding variables in the interaction between conscientiousness and life satisfaction. Future research should consider cognitive flexibility and failure experiences as mediating variables. Keywords: cognitive flexibility; life satisfaction; phubbing; trait conscientiousness.